Visuospatial reasoning of eighth-grade students in solving geometry problems: A gender perspective - Kartika Sulistiya Nuriswaty; Sadrack Luden Pagiling; Nurhayati Nurhayati (Universitas Islam Negeri (UIN) Mataram, 2020)
[English]: Visuospatial reasoning is indispensable in solving mathematical problems, especially geometry. However, many students face difficulty in visuospatial reasoning. This qualitative study aims to describe eighth-grade students' visuospatial reasoning in solving geometry problems in terms of gender differences. One male and one female student with high mathematics ability were involved. A test and interview were utilized to collect data. The test was used to investigate students' visuospatial reasoning and the interview was administered to confirm students' reasoning. Students’ test and interview results were analyzed in three stages: data condensation, data presentation, and conclusion drawing and verification. This study found that both male and female students' visuospatial reasoning in solving the problems is at the synthesis level. However, at the synthesis level, when identifying the spatial relationships between objects, the male student expresses information from the overall view scheme, while the female student expresses part by part of the view scheme. Keywords: Visuospatial reasoning, Geometry problems, Gender [Bahasa]: Penalaran visuospasial sangat diperlukan dalam menyelesaikan masalah matematika terutama pada masalah geometri. Namun, banyak siswa yang mengalami kesulitan dalam melakukan penalaran visuospasial. Penelitian kualitatif ini bertujuan mendeskripsikan penalaran visuospasial siswa kelas VIII yang ditinjau dari perbedaan gender dalam menyelesaikan masalah geometri. Satu siswa laki-laki dan satu siswa perempuan dengan kemampuan matematika tinggi dipilih sebagai subjek. Tes dan wawancara digunakan untuk mengumpulkan data. Tes digunakan untuk menyelidiki penalaran visuospatial siswa dan wawancara bertujuan mengonfirmasi dan menggali lebih dalam penalaran siswa. Data hasil tes dan wawancara dianalisis dalam tiga tahap, yaitu reduksi data, penyajian data, dan penarikan dan verifikasi simpulan. Hasil penelitian menunjukkan bahwa penalaran visuospasial siswa laki-laki dan perempuan dalam menyelesaikan masalah geometri berada pada jenjang sintesis. Namun, terdapat perbedaan pada jenjang sintesis dalam mengidentifikasi keterkaitan spasial antar objek-objek. Siswa laki-laki mengutarakan informasi dari skema pandangan secara menyeluruh, sedangkan siswa perempuan mengutarakan bagian per bagian dari skema pandangan tersebut. Kata kunci: Penalaran visuospasial, Masalah geometri, Gender